Assistive technology access for all students - Beard, Lawrence A. (Pearson, 2011)
Organized around the theme of universal design, this guide to assistive technology discusses the knowledge and skills educators need to know in order to determine the appropriate use of technology and services to meet the needs of individuals with disabilities.